Philoxenia — the DNA of hospitality: hype or cure? - Peter A. Singleton (Research in Hospitality Management, 2023)
Philoxenia is the ancient Greek custom or tradition of treating a stranger as a friend, but it goes much deeper in terms of its reality and consequences. This custom sits deep in Greek culture and mythology, where its layers of culture and religion formed a powerful force for creating peaceful relations at individual, group or societal levels. A modern-day example of survival of the ancient and unconditional form of philoxenia is the island of Icaria, situated in the Aegean Sea. The Icarian culture and its way of life has remained faithful to traditional customs, aided by an isolated geographical location. Icaria is an isolated island unprotected from the wind. It is, however, also a “Blue Zone” where the average life expectancy is one of the highest in the world and where heart disease and cancers are extremely rare. This research note defines and discusses the ancient tradition of philoxenia (otherwise known as hospitality), highlighting its unconditionality as a force for harmony, social cohesion and inspired outcomes, contrasted with the conditionality of the modern forms of hospitality that are based on the exchange of money for services. It discusses how understanding philoxenia can illuminate dysfunctionality in modern hospitality service-scapes, and considers a wider geopolitical perspective that conflicts can be reduced at national level (according to some scholars), just as ignoring philoxenia and instead allowing xenophobia to go unchecked can encourage conflicts. Research is drawn from ancient and modern sources, and the proposition developed is that philoxenia is a moral imperative, an unconditional commitment to the stranger, at peril of dissolution due to materialism and dysfunctionality in our modern setting, which in turn is giving rise to avoidable levels of conflict between individuals, groups or nations.